Findings of ocular and brain hemodynamics in patients with anterior uveitis complicated by macular edema - N.I. Khramenko; N.V. Konovalova (Ukrainian Society of Ophthalmologists, 2020)
Background: Uveitis is the fifth most common cause of visual loss in the developed world, accounting for about 10% of legal blindness. Macular edema (ME) has been found to be the most important cause of both blindness and visual impairment (29% and 41%, respectively) in patients with uveitis. The rate of macular edema in patients with anterior uveitis may be as high as one-third. Molecular mechanisms and pathophysiology of inflammatory retinal detachment in uveitis have been only partially elucidated. It is still unclear why some patients exhibit only one episode of ME, while others have a chronic or recurrent course of ME and are resistant to immunomodulatory and anti-inflammatory therapy. Purpose: To identify the features of ocular and brain hemodynamics in patients with anterior uveitis complicated by ME. Material and Methods: Totally, 155 uveitis patients (primary anterior uveitis, 30 patients; recurrent anterior uveitis, 125 patients) who were examined and treated at Uveitis Department and Visual Function Research Laboratory were involved in this study. Not only routine studies, but also optical coherence tomography, electrical impedance studies (ophthalmic rheography and rheoencephalography), and adaptation potential studies were performed. Results: Most cases (73.3%) with primary uveitis had a unilateral disease (p = 0.05), and as much as 50% of patients with recurrent uveitis had a bilateral disease. Macular edema was found in 18.4% of cases with primary uveitis, 20.8% of cases with frequently recurring uveitis, 3.3% of cases with infrequently recurring uveitis, and 11.5% of cases with non-identified recurrence pattern of uveitis. The rate of ME was higher in a bilateral primary disease (37.5%) than in a unilateral primary disease (p = 0.009). Macular edema was found 17% more frequently (p = 0.03) in frequently recurring uveitis than in infrequently recurring uveitis. Among patients with ME, those with frequent recurrences of anterior uveitis had the lowest mean visual acuity (0.28 ± 0.07). Compared to patients without ME, those with ME exhibited a 50% and 22.2% higher ocular pulse blood filling (OPBF, expressed as RQ, ‰ rheographic coefficient) in primary anterior uveitis and in recurrent anterior uveitis, respectively. In addition, compared to patients with uncomplicated anterior uveitis, those with ME exhibited a 71% and a 33.3% higher ocular blood flow velocity in primary anterior uveitis and in recurrent anterior uveitis, respectively. Relative pulse blood filling of the internal carotid system in patients with recurrent anterior uveitis complicated by ME was 30% higher than in patients with uncomplicated recurrent anterior uveitis. Our study of the adaptation potential, an integrative indicator of the cardiovascular system's response to the stimulus, found that, among the anterior uveitis patients, the vast majority (84%) showed stressed adaptation mechanisms. Conclusion: Macular edema was found in 18.4% of cases with primary uveitis, 20.8% of cases with frequently recurring uveitis, and 3.3% of cases with infrequently recurring uveitis. The disease bilaterality in primary anterior uveitis and frequent recurrences in recurrent anterior uveitis were found to be aggravating factors for the development of ME. Compared to patients with uncomplicated anterior uveitis, those with ME exhibited a 50% and 22.2% higher OPBF expressed as RQ in primary anterior uveitis and in recurrent anterior uveitis, respectively. Relative pulse blood filling of the internal carotid system in patients with recurring anterior uveitis complicated by ME was 30% higher than in patients with recurring uncomplicated anterior uveitis.